THE EFFECT OF INJECTING RECURRENT DOSES OF HEPATITIS B VACCINE TO THE CHANGE OF PANCREATIC ORGAN WEIGHT AND BLOOD GLUCOSE LEVELS IN FEMALE RABBITS (Oryctolagus cuniculus) - MAURA ALVARITA DEVA MEGANANDA, 061411131164 (2018)
The aim of this research was to determine the change of pancreatic organ weight and blood glucose levels in female rabbits (Oryctolagus cuniculus) injected with recurrent doses of hepatitis B vaccine or also known as booster method. There were 12 rabbits that divided into 4 groups consist of 1 control group, and 3 treatment groups with different concentration of vaccine formulation. Before the treatment, the rabbits have been adapted in new environment for 7 days in Experimental Animal Laboratory of Faculty Of Veterinary Medicine Airlangga University, given by feed and water daily. After adaptation period, all treatment rabbits had the vaccination at day 0. Control group was given by PBS solution 0.4ml injected intramuscular via 4 legs, 0.1ml for each leg and treatment groups were given by hepatitis B vaccine 0.4ml injected intramuscular via 4 legs, 0.1ml for each leg. Then repeated at day 30 and 60 with the same vaccine formula and dose with day 0. Post treatment pancreatic organ and blood sample were collected at day 75, the blood was collected and then analyzed by glucometer kit diagnostic and the pancreas was scaled in digital scale. Based on the anova results, pancreatic organ weight shows value 0.131 > 0.05 and blood glucose value is 0.477 > 0.05. The post treatment result leads statistically non significant increase (p > 0.05). It means the vaccine did not cause significant changes of pancreatic organ weight and blood glucose levels.